Developmental and evolutionary dynamics of cis-regulatory elements in mouse cerebellar cells - Sarropoulos, Ioannis; Sepp, Mari; Frömel, Robert; Leiss, Kevin; Trost, Nils; Leushkin, Evgeny; Okonechnikov, Konstantin; Joshi, Piyush; Giere, Peter; Kutscher, Lena M.; Cardoso-Moreira, Margarida; Pfister, Stefan; et al. (Science, 2021)
Organ development is orchestrated by cell- and time-specific gene regulatory networks. In this study, we investigated the regulatory basis of mouse cerebellum development from early neurogenesis to adulthood. By acquiring snATAC-seq profiles for ~90,000 cells spanning eleven stages, we mapped cerebellar cell types and identified candidate cis-regulatory elements (CREs). We detected extensive spatiotemporal heterogeneity among progenitor cells and a gradual divergence in the regulatory programs of cerebellar neurons during differentiation. Comparisons to vertebrate genomes and snATAC-seq profiles for ∼20,000 cerebellar cells from the marsupial opossum revealed a shared decrease in CRE conservation during development and differentiation, but also differences in constraint between cell types. Our work delineates the developmental and evolutionary dynamics of gene regulation in cerebellar cells and provides insights into mammalian organ development.